Analysis of MSME Digital Marketing Strategy "kripik.t_mpeÃ¢â‚¬Â on Instagram - Gustiawan, Wahyu Dede; Rahayu, Budi (Manajemen dan Kewirausahaan, 2024)
This research discusses digital marketing carried out by Kripik.t_mpe MSMEs located in Kediri, East Java, considering the importance of using online marketing media today, cannot be maximized by MSME actors. How to create the right and quality content is rarely noticed by business owners so that the impact has not been felt optimally either. This study used qualitative research methods. with researchers interviewing MSME owners directly, using data analysis methods by collecting data, reducing and concluding data. The result of this study is that MSMEs Kripik.t_mpe have run several ways to make their marketing content quality such as relevance, creativity, visual quality, storytelling, interaction, consistency, and authenticity. Although in some ways such as improving visual quality and consistency has not been carried out properly.